Inhibitory Test of Scleria sumatrensis Stem Extract against Propionibacterium acnes Bacteria in Vitro - Sonny D. Untu; Douglas N. Pareta; Selvana S. Tulandi; Jabes W. Kanter; Andri Natanel (FMIPA UKIT, 2025)
This study aims to test the antibacterial activity of Scleria sumatrensis extract against Propionibacterium acnes, a bacteria that causes acne. Extraction was carried out using the maceration method using 96% ethanol, and the antibacterial activity test was carried out using the diffusion method using a concentration of 100–500 ?g/disc. The results showed that the extract provided moderate antibacterial activity at a concentration of 100 ?g/disc and increased to strong at a concentration of 200–500 ?g/disc. S. sumatrensis extract contains secondary metabolite compounds such as phenolics, flavonoids, alkaloids, tannins, steroids, and terpenoids that play a role in inhibiting the growth of P. acnes through various mechanisms, including cell membrane damage, inhibition of protein synthesis, and disruption of bacterial metabolism. Based on the results of the study, S. sumatrensis extract has the potential as a natural antibacterial alternative for acne treatment without significant side effects or the risk of antibiotic resistance.